1999
DOI: 10.1021/js980205u
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Racemic Species of Chiral Drugs Using Thermal Analysis, Thermodynamic Calculation, and Structural Studies

Abstract: The identification of the racemic species, as a racemic compound, a racemic conglomerate, or a racemic solid solution (pseudoracemate), is crucial for rationalizing the potential for resolution of racemates by crystallization. The melting points and enthalpies of fusion of a number of chiral drugs and their salts were measured by differential scanning calorimetry. Based on a thermodynamic cycle involving the solid and liquid phases of the enantiomers and racemic species, the enthalpy, entropy and Gibbs free en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 21 publications
6
86
0
1
Order By: Relevance
“…; the formula for enthalpy of formation and entropy of formation of racemate by using the thermodynamic cycle involves solid phase enantiomers and racemate D S , L S , R S and liquid phase enantiomers and racemate D L , L L , R L has been derived as 14,15 : Enthalpy of formation:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; the formula for enthalpy of formation and entropy of formation of racemate by using the thermodynamic cycle involves solid phase enantiomers and racemate D S , L S , R S and liquid phase enantiomers and racemate D L , L L , R L has been derived as 14,15 : Enthalpy of formation:…”
Section: Methodsmentioning
confidence: 99%
“…15 Although this observation is not conclusive for all compounds (as indicated before, the melting point phase diagram is not an adequate criterion for identifying the nature of the racemic species), for example, ephedrine á HCl 15 is a racemic compound even though it has DT f of )28.3 K, large differences in the melting points (DT f approaching )30 K) between the homochiral and racemic species have been widely utilized to examine the nature of chiral drugs due to its easy application. In addition, the entropy of mixing of (R)-and (S)-PN á Cl in the liquid state was calculated according to Eq.…”
Section: Enthalpy Entropy and Free Energy Of Formation Of Propranolmentioning
confidence: 99%
“…Structural properties of IBP enantiomers and racemate have been widely characterized, by different experimental techniques and simulation [3][4][5][6][7][8][9][10][11]. In particular, it was observed that in crystal lattices of both (S)-and (R, S)-IBP two molecules are arranged to form a cyclic dimer through hydrogen bonds between their carboxylic groups COOH.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was observed that in crystal lattices of both (S)-and (R, S)-IBP two molecules are arranged to form a cyclic dimer through hydrogen bonds between their carboxylic groups COOH. Thermodynamics of sublimation, crystal lattice energies, and crystal structures of racemate and enantiomers of IBP have been also characterized [4,5] in order to understand the differences of drug-drug intermolecular interactions in the two cases. This information is the basic knowledge needed for a rational development of the appropriate method for the resolution of racemate.…”
Section: Introductionmentioning
confidence: 99%
“…B. Lit. [141]) und Klussmann. [142,143] Unseres Wissens gibt es bislang keine Monographie, die im Schwerpunkt Phasengleichgewichte organischer Verbindungen behandelt.…”
Section: Fest-flüssig-gleichgewichte Und Abgeleitete Mçglichkeiten Zuunclassified